2008
DOI: 10.1097/qai.0b013e3181684c51
|View full text |Cite
|
Sign up to set email alerts
|

Brief Strengths-Based Case Management Promotes Entry Into HIV Medical Care

Abstract: The ARTAS linkage case management intervention provides a model that health departments and CBOs can use to ensure that recently diagnosed HIV-infected persons attend an initial HIV care encounter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(167 citation statements)
references
References 28 publications
5
162
0
Order By: Relevance
“…Respondents in our study appear to have had one or fewer encounters with a case manager, which may not be optimal. Previous studies had shown that for newly diagnosed HIV-infected persons, linkage to care activities are more successful when persons have an average of two or more encounters with a case manager (Craw et al, 2008;Gardner et al, 2005). These data support previous findings describing the benefit of ongoing linkage to care activities that may include multiple follow-up encounters to increase the chances of successful linkage to care.…”
Section: Perception Of Follow-up Servicessupporting
confidence: 82%
See 1 more Smart Citation
“…Respondents in our study appear to have had one or fewer encounters with a case manager, which may not be optimal. Previous studies had shown that for newly diagnosed HIV-infected persons, linkage to care activities are more successful when persons have an average of two or more encounters with a case manager (Craw et al, 2008;Gardner et al, 2005). These data support previous findings describing the benefit of ongoing linkage to care activities that may include multiple follow-up encounters to increase the chances of successful linkage to care.…”
Section: Perception Of Follow-up Servicessupporting
confidence: 82%
“…Respondents agreed that passive referrals were of little help and provided minimal, if any, assistance in accessing care. As shown in previous studies, active referrals are more successful for linking newly diagnosed persons to care (Craw et al, 2008, Gardner et al, 2005. The addition of a detailed, standard definition of an active referral in future CTR guidelines may be necessary to support the provision of an optimal level of service when referring to or providing linkage to care services.…”
Section: Perception Of Follow-up Servicesmentioning
confidence: 96%
“…Approximately 30% of the diagnosed youth are linked to care and retained for one year. Brief intensive case management and patient navigator systems have worked well with adults 36,37,94 and are being used in adolescent networks. 95 Peer or clinic-based system navigators form personal and professional relationships that break down some of the barriers to initiating care.…”
Section: Discussionmentioning
confidence: 99%
“…Four separate studies found low rates of linkage to care for adolescents and young adults, ranging from between 29% and 73% within the first year of diagnosis. 35,[37][38][39] The ARTAS trial, an intervention designed to increase linkage to care using five sessions with a linkage case manager, successfully linked 73% of those aged 18-25 to care within the first 6 months, compared to 81% for older adults. 37 Another intervention study, the California Bridge Project, successfully linked only 29% of those younger than 25 years of age who were previously out of care.…”
Section: Linkage To Carementioning
confidence: 99%
“…This result was confirmed by follow-up testing. Linkage of patients newly diagnosed HIV positive to further care is very important and relatively brief interventions can be effective (Craw, JA., et al, 2008). On the basis of other laboratory indices, such as CD4 count and viral load, it appears that the patient has been infected for many years.…”
Section: Casementioning
confidence: 99%